Feasibility Prediction of Quercetin and Ascorbic Acid Combination for Skin Lightening through Tyrosinase Inhibition Mechanism by Molecular Docking - Nadia Paramitha Nugroho; Widji Soeratri; Noorma Rosita (Universitas Airlangga, 2025)
Background: Hyperpigmentation is an aesthetic problem that can affect people psychologically and emotionally. Quercetin and ascorbic acid are topical ingredients commonly used as skin lightening active ingredients by their role as tyrosinase inhibitors. Objective: This research is to determine quercetin’s feasibility to be combined with ascorbic acid or one of its more stable and commercially most used derivatives in cosmetics, 3-O-ethyl ascorbic acid in inhibiting tyrosinase. Methods: The research was conducted in an in silico manner by molecular docking, supplemented by literature research on in vitro experiments. The ligands and receptor preparation were undertaken prior to performing molecular docking with AutoDockTools 1.5.6. Molecular docking was carried out after the validation step with the RMSD value of 0.91 Å. Results: Quercetin has greater binding affinity to tyrosinase (ΔG = -5.01 kcal/mol) than ascorbic acid (ΔG = -4.20 kcal/mol), as well as owning the most similar type of interaction and comparable affinity to L-tyrosine (ΔG = -5.87 kcal/mol) as the native ligand. Quercetin shares several same amino acid residues with ascorbic acid which indicates similar mechanisms of inhibition. Meanwhile, ascorbic acid possesses virtually equal binding affinity to 3-O-ethyl ascorbic acid (ΔG = -4.63 kcal/mol), though has considerably more potent tyrosinase inhibition activity in in vitro studies. Conclusion: Ascorbic acid is postulated to be feasible to combine with quercetin for inhibiting tyrosinase activity to eventually yield more optimized depigmenting effect.